ECB quantitative easing, euro depreciation and supply chains: Industry-level estimates for Germany, Italy and Greece. New prospects for a Minskyan big bank? - Gobbi, Lucio; Lucarelli, Stefano (PSL Quarterly Review, 2021)
We investigate how the 2014-2016 depreciation of the euro against the US dollar triggered a cascade effect on the European supply chains which reduced the current account imbalances among the EU member states. In particular, we analyze the specific case of Greece to verify whether the higher export demand towards the USA in the two main European exporting countries, Germany and Italy, increased the demand for Greek goods and services by the German and Italian economies. We employee a linear ARDL model which is able to track short- and long-term effects of the depreciation on the industries of Greece with respect to Germany, Italy and the USA for the period 2010-2016 using bilateral monthly data. The empirical findings show that the euro depreciation increased the integration between the German and Greek production structures in various industries representing more than 35% of the entire trade between the two countries. JEL codes: F31; F32 Keywords: Industry trade; bounds testing; J-curve; Minskyan big bank